Effects of Nonpharmacological Interventions on Disruptive Vocalisation in Nursing Home Patients With Dementia-A Systematic Review - Saad Bilal Ahmed; Alfredo Obieta; Tamsin Santos; Saara Ahmad; Joseph Elliot Ibrahim (Frontiers Media S.A., 2022)
BackgroundVocally disruptive behaviour is a common and difficult to treat condition in older residents with dementia. The aim of this systematic review is to evaluate the efficacy of nonpharmacological interventions in its management in persons with dementia residing in a nursing home.MethodologyA systematic search was conducted using Ovid MEDLINE, CINAHL, and Cochrane databases and reference lists from relevant publications on various nonpharmacological approaches to manage vocally disruptive behaviour in nursing home residents. The method of appraisal was through the National Institutes of Health scoring for the Quality Assessment of controlled intervention studies. Inclusion criteria included residents of nursing homes over the age of 65 with dementia and disruptive vocalisation. Only randomised controlled trials published in English were included.ResultsA total of 5,606 articles were identified, which cover 501 trials, of which 23 were selected. There were fourteen studies observed to have an impact of clinical and statistical significance with interventions including (i) a multidimensional approach with different nonpharmacological interventions, (ii) multisensory stimulation, (iii) staff education and training, (iv) personalised bathing, and (v) pain recognition and appropriate management. Seven studies demonstrated no observable effect whereas two showed worsening in vocally disruptive behaviour.ConclusionsMany aspects of vocally disruptive behaviour management are poorly understood. Limited empirical evidence supports the use of several nonpharmacological interventions to reduce it. There is more robust evidence to support the use of a tailored approach to management over the universal approach.